Implementasi pendidikan karakter di era 4.0 pada peserta didik kelas III di sekolah dasar - Elok Dwi Pratidina; Sri Marmoah; Sularmi Sularmi (Universitas Sebelas Maret, 2021)
This research aims to describe the implementation of character education in the era 4.0 in 3th grade students of SDN Kerten II No. 243 Surakarta in 2020/2021 academic year. This research is a quality description with a type of study case. The subject is seven people of 3th grade students of SDN Kerten II. The data collection is using survey, interviews and observations with eight indicators of character education is religious, honestly, discipline, responsibility, caring and cooperation. Validity data is using triangulation techniques and triangulating sources. Using interactive data analysis by Miles-Huberman. These research results indicate that the most visible character value is religious and less responsibility. The cursed from the inside is the lack of child's attention during the implementation of character education while the cursed from the outside is the lack of parental interest and the indicators of character assessment it’s hard to be measured. The solution that was given is to border a child in using technology, increasing good relationships with parents and designing indicators of measurable character judgment. This conclusion is the implementation of character education in the 4.0 era in 3th grade students of SDN Kerten II No. 243 Surakarta 2020/2021 academic year is good.